Military Aggression and Risk Predicted by Explanatory Style - Satterfield, Jason M.; Seligman, Martin E.P. (Psychological Science, 1994)
The explanatory style scores of George Bush and Saddam Hussein were derived using the content analysis of verbatim explanations technique for periods preceding military actions or political conflict These leaders' actions were rated on scales of aggression-passivity and risk-caution Regression and correlational analyses show that increased levels of optimism before conflict predicted heightened aggression and risk taking, whereas increased levels of pessimism prior to an event predicted passivity and caution